From neuroimunomodulation to bioelectronic treatment of rheumatoid arthritis. Issue 2 (25th May 2018) - Kanashiro, Alexandre; Bassi, Gabriel Shimizu; Queiróz Cunha, Fernando de; Ulloa, Luis
Neuronal stimulation is an emerging field in modern medicine to control organ function and reestablish physiological homeostasis during illness. The nervous system innervates most of the peripheral organs and provides a fine tune to control the immune system. Most of these studies have focused on vagus nerve stimulation and the physiological, cellular and molecular mechanisms regulating the immune system. Here, we review the new results revealing afferent vagal signaling pathways, immunomodulatory brain structures, spinal cord-dependent circuits, neural and non-neural cholinergic/catecholaminergic signals and their respective receptors contributing to neuromodulation of inflammation in rheumatoid arthritis. These new neuromodulatory networks and structures will allow the design of innovative bioelectronic or pharmacological approaches for safer and low-cost treatment of arthritis and related inflammatory disorders.